2014
DOI: 10.4161/adip.29674
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cre recombinase models for the study of adipose tissue

Abstract: The study of adipose tissue in vivo has been significantly advanced through the use of genetic mouse models. While the aP2-CreBI and aP2-CreSalk lines have been widely used to target adipose tissue, the specificity of these lines for adipocytes has recently been questioned. Here we characterize Cre recombinase activity in multiple cell populations of the major adipose tissue depots of these and other Cre lines using the membrane-Tomato/membrane-GFP (mT/mG) dual fluorescent reporter. We find that the aP2-CreBI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
193
2
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(220 citation statements)
references
References 36 publications
14
193
2
5
Order By: Relevance
“…In complementary studies, we also examined whether βKlotho is expressed in TECs expressing FoxN1, a transcription factor that is critical for thymopoiesis (26). To do this, we used transgenic mice harboring a fluorescent membrane dTomato/membrane EGFP (mT/mG) Cre reporter construct (27) that marks FoxN1 Cre excision by a heritable switch from membrane-targeted tdTomato expression to membrane-targeted EGFP expression. Examination of Foxn1-Cre:mT/mG mice thymi revealed that βKlotho is colocalized with Foxn1 + TECs (Fig.…”
Section: Significancementioning
confidence: 99%
“…In complementary studies, we also examined whether βKlotho is expressed in TECs expressing FoxN1, a transcription factor that is critical for thymopoiesis (26). To do this, we used transgenic mice harboring a fluorescent membrane dTomato/membrane EGFP (mT/mG) Cre reporter construct (27) that marks FoxN1 Cre excision by a heritable switch from membrane-targeted tdTomato expression to membrane-targeted EGFP expression. Examination of Foxn1-Cre:mT/mG mice thymi revealed that βKlotho is colocalized with Foxn1 + TECs (Fig.…”
Section: Significancementioning
confidence: 99%
“…However, a recent study suggests that Ap2 is not specific for the adipocytes, but it is highly expressed also in endothelial cells. 41 Indeed, previous transgenic studies based on the Ap2 promoter are now being revisited by the generation of the corresponding Adiponectin promoter-based transgenic model with very different phenotypic outcomes. 42,43 In this respect, the metabolic outcome shown in the work of Qian et al, 23 where an Ap2-Bmp4 mouse model was used needs to be re-evaluated as Bmp4 might be produced in various organs from the endothelial cells, and after secretion regulate the function of cells and tissues in a paracrine and maybe also endocrine manner.…”
mentioning
confidence: 99%
“…Недавно было показано, что клетки-предшественники адипоцитов белой жировой ткани экспрессируют PDGFRα (CD140a), который также является маркером всех адипоцитов в белом жире [17]. Имеющаяся линия трансгенных мышей PDGFRα-Cre является одной из наиболее адекватных для исследований клеток-пред-шественников жировой ткани, так как позволяет произ-водить делецию в преадипоцитах [18].…”
Section: развитие адипоцитовunclassified
“…Это приводит к его активации, осуществляя своеобразную связь между Сахарный диабет. 2015;18(2): [12][13][14][15][16][17][18][19] инсулиновым и цАМФ-зависимым каскадами. Наконец, инсулин приводит к активации гена Srebf1, играющего значительную роль на последующих стадиях адипоге-неза [44].…”
Section: транскрипционные факторы адипогенезаunclassified
See 1 more Smart Citation